2016
DOI: 10.14814/phy2.12885
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin intake attenuates muscle atrophy caused by immobilization in rats

Abstract: Astaxanthin is a carotenoid pigment and has been shown to be an effective inhibitor of oxidative damage. We tested the hypothesis that astaxanthin intake would attenuate immobilization‐induced muscle atrophy in rats. Male Wistar rats (14‐week old) were fed for 24 days with either astaxanthin or placebo diet. After 14 days of each experimental diet intake, the hindlimb muscles of one leg were immobilized in plantar flexion position using a plaster cast. Following 10 days of immobilization, both the atrophic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
1
32
1
Order By: Relevance
“…The effect of astaxanthin on delaying physical exhaustion may involve the redox imbalance in both serum and muscle [51]. Moreover, multiple studies have demonstrated that astaxanthin improved muscular function by inhibiting oxidative stress in the muscle, such as reduce ROS production, increase antioxidant genes expression and anti-oxidative enzymes activities, and decrease mitochondria damage [51][52][53]. Therefore, astaxanthin administration significantly restored the loss of muscular function in our study (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…The effect of astaxanthin on delaying physical exhaustion may involve the redox imbalance in both serum and muscle [51]. Moreover, multiple studies have demonstrated that astaxanthin improved muscular function by inhibiting oxidative stress in the muscle, such as reduce ROS production, increase antioxidant genes expression and anti-oxidative enzymes activities, and decrease mitochondria damage [51][52][53]. Therefore, astaxanthin administration significantly restored the loss of muscular function in our study (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, the weight of the left and the right muscles of both the control group and the ZM-E group, after strapping the left ankle joint for 2 weeks, showed a significant decrease in the weight of both the control group and the ZM-W and ZM-E groups. A statistically significant change in the ratio of the proximal axis (according to the method by Shibaguchi et al [31]) was observed when the left muscle mass change was compared to the right, with a reduction of about 22.0% for the control group, 19.5% for the ZM-W group, and 18.8% for the ZM-E group (Table 1). These results indicated that pharmacopuncture using ZM showed significant protection against weight loss in the gastrocnemius muscle caused by disuse muscle atrophy.…”
Section: Discussionmentioning
confidence: 94%
“…AST is an antioxidant found in algae, fish, crustaceans, and birds . AST has potent antioxidant activity shown by scavenging reactive oxygen species (ROS) such as superoxide anion, hydrogen peroxide, singlet oxygen, and also inhibit in vitro lipid peroxidation . Cd is toxic and has low excretion rate from body therefore is an important toxic metal .…”
Section: Discussionmentioning
confidence: 99%
“…[36] AST has potent antioxidant activity shown by scavenging reactive oxygen species (ROS) such as superoxide anion, hydrogen peroxide, singlet oxygen, and also inhibit in vitro lipid peroxidation. [37] Cd is toxic and has low excretion rate from body therefore is an important toxic metal. [38] One of the most important effects of heavy metals such as Cd is oxidative stress.…”
Section: Discussionmentioning
confidence: 99%